Book Reviews. Issue 2 (1st October 2014) - Calvert, Bronwen; Adams, Mark Richard; Medhurst, Jamie; Dvorak, Ken
Joss Whedon: A Creative Portrait, David Lavery (2013) London: I. B. Tauris, 272 pp., ISBN: 9781848850309, p/bk, £10.99.Doctor Who: The Eleventh Hour – A Critical Celebration of the Matt Smith and Steven Moffat Era, Andrew O'Day (ed.) (2013) London: I. B. Taurus, 288 pp. ISBN: 9781780760193, p/bk, £12.99Transnational Television History: A Comparative Approach, Andreas Fickers and Catherine Johnson (Eds) (2012) London: Routledge, 176 pp., ISBN: 0145698603, h/bk, £85.00Transnational Television Drama: Special Relations and Mutual Influence between the US and the UK, Elke Weissmann (2012) Basingstoke: Palgrave Macmillan, 240 pp., ISBN: 0230297753, h/bk, £50.00The Triumph of Reality TV: The Revolution in American Television, Leigh H. Edwards (2013) California: Praeger, pp.199., ISBN: 9780313399015, h/bk, 37.00